Plausible lies and implausible truths: Police investigators' preferences while portraying the role of innocent suspects. (17th June 2019) - Elaad, Eitan
Abstract : Purpose: The present study was designed to examine differences between the preferences of police investigators and laypeople for lies over implausible truths, when assigned to the role of innocent suspects in simulated police investigation scenarios, in order to convince the interrogator of their innocence. Methods: Thirty police investigators and thirty laypeople were asked to report how they would behave in four imaginary implausible crime scenarios, given their role as innocent suspects. Participants responded by selecting one of the following four alternative behaviours for each scenario: implausible truth, concealment, partial lie, and utter lie. Results: Results showed that police investigators tended to select plausible lies rather than less plausible truths. Laypeople adhered to less plausible truths. Results were explained by investigators' biased self‐assessed lie‐detection and truth‐telling abilities, which correlated positively with lying preferences. Conclusions: It was suggested that innocent suspects should abandon the unrealistic belief that truth will prevail and be ultimately validated. They are advised instead to prepare a convincing story prior to the criminal interrogation and, if necessary, to conceal unexplained implausible statements from interrogators.